Olympic Mobile Application Succeeds: A Case Study on Sotshi Areena - Lankinen, Tiina (Πανεπιστήμιο Πελοποννήσου, 2016)
The aim of this study was to research the user response to a new kind of Olympic experience; mobile viewing of the Games in Finland through a public broadcast service titled Sotshi Areena in 2014. In addition, the historical and cultural development towards mobile sports audiences was studied. The data used were the responses of 4.773 individuals who took part in a post-survey of the Olympic production in Finnish public broadcasting company Yle. In comparison to television broadcasts' watchers, the users of the mobile service Sotshi Areena were more critical in their feedback and less satisfied. Nevertheless the Sotshi Areena service was applauded by users. Sotshi Areena acted as a secondary, if inferior, screen to witness the Olympic Games. Thus viewers who only relied on television broadcasts were less satisfied with the overall Olympic production in Yle than those who had Sotshi Areena in their repertoire. Even though Sotshi Areena received criticism concerning haste in its making, releasing the service helped viewers to enjoy the Games more fully. Vehement feedback about vast technical difficulties are overcome by the sheer possibility to follow events whenever and wherever a television is not available. Live sports are a very distinct television entity in their own because of the exceptional time sensitivity it demands. The question of what to watch was not necessarily that relevant, judging by the open feedback. But, as viewing habits are swiftly changing, audiences may well grow accustomed to individual sports content choices at the expense of national togetherness.
Keywords: Broadcasting; Mass media and sports - Case study; Olympics; Αναμετάδοση; Μέσα μαζικής ενημέρωσης και αθλητισμός - Περιπτωσιακή μελέτη; Ολυμπιακοί αγώνες; Olympics; Broadcasting; Mobile application; Ολυμπιακοί αγώνες; Αναμετάδοση; Εφαρμογή κινητού